IMPLEMENTATION OF PANCASILA IN THE STRATEGY TO ERADICATE CORRUPTION IN INDONESIA - muarofah, choirul; nadia leila; khoirun nufus; wahidullah; amin syifa; nadia yumna; feri pradana; zakib fahiroh; ifa nur (Journal Civics And Social Studies, 2024)
ABSTRACT The application of Pancasila values ​​has a strategic role in efforts to eradicate corruption in Indonesia. Pancasila, as the basis of the state and the nation's way of life, contains noble values ​​such as justice, honesty, responsibility and concern for common interests, which are the moral and ethical foundations in national and state life. In the context of eradicating corruption, the application of Pancasila values ​​can be realized through strengthening individual integrity, fair law enforcement, increasing public awareness, and developing an anti-corruption culture in various sectors. This article examines the relationship between Pancasila values ​​and strategies for eradicating corruption, including the obstacles faced and the solutions offered. By integrating Pancasila values ​​in anti-corruption policies and education, it is hoped that a cleaner, more transparent and more responsible society will be created. This research emphasizes the important role of all parties, from the government, educational institutions, to society, in realizing an Indonesia free from corruption through consistent and continuous implementation of Pancasila. Keywords: Pancasila, eradicating corruption, integrity. Abstrak Penerapan nilai-nilai Pancasila memiliki peran strategis dalam upaya pemberantasan korupsi di Indonesia. Pancasila, sebagai dasar negara dan pandangan hidup bangsa, mengandung nilai-nilai luhur seperti keadilan, kejujuran, tanggung jawab, dan kepedulian terhadap kepentingan bersama, yang menjadi landasan moral dan etika dalam kehidupan berbangsa dan bernegara. Dalam konteks pemberantasan korupsi, penerapan nilai-nilai Pancasila dapat diwujudkan melalui penguatan integritas individu, penegakan hukum yang adil, peningkatan kesadaran masyarakat, serta pengembangan budaya antikorupsi di berbagai sektor. Artikel ini mengkaji keterkaitan antara nilai-nilai Pancasila dengan strategi pemberantasan korupsi, termasuk hambatan-hambatan yang dihadapi dan solusi yang ditawarkan. Dengan mengintegrasikan nilai-nilai Pancasila dalam kebijakan dan pendidikan antikorupsi, diharapkan tercipta masyarakat yang lebih bersih, transparan, dan bertanggung jawab. Penelitian ini menekankan pentingnya peran semua pihak, mulai dari pemerintah, lembaga pendidikan, hingga masyarakat, dalam mewujudkan Indonesia bebas dari korupsi melalui pengamalan Pancasila secara konsisten dan berkesinambungan. Kata Kunci : Pancasila, pemberantasan korupsi, integritas.